2002
DOI: 10.1046/j.1432-1033.2002.03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Bax‐induced cell death in yeast depends on mitochondrial lipid oxidation

Abstract: The oxidant function of pro-apoptotic protein Bax was investigated through heterologous expression in yeast. Direct measurements of fatty acid content show that Baxexpression induces oxidation of mitochondrial lipids. This effect is prevented by the coexpression of Bcl-x L . The oxidation actually could be followed on isolated mitochondria as respiration-induced peroxidation of polyunsaturated cisparinaric acid and on whole cells as the increase in the amount of thiobarbituric acid-reactive products. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 67 publications
3
39
0
Order By: Relevance
“…29 It has also been shown that Bax expression, even at low-expression levels, induced the oxidation of mitochondrial lipid, including CL, an effect which is prevented by hydrophobic antioxidants, such as a-tocopherol and resveratrol. 37 It is important to notice that yeast expression of tBid alone has no effects on the whole yeast cell respiration (data not shown) nor on cell growth. 34 However, in the presence of Bax-c-myc, the expression of tBid increased the kinetics of Bax-c-myc-induced cell death, 34 showing that tBid is able to amplify the killing function of an active form of Bax.…”
Section: Discussionmentioning
confidence: 94%
“…29 It has also been shown that Bax expression, even at low-expression levels, induced the oxidation of mitochondrial lipid, including CL, an effect which is prevented by hydrophobic antioxidants, such as a-tocopherol and resveratrol. 37 It is important to notice that yeast expression of tBid alone has no effects on the whole yeast cell respiration (data not shown) nor on cell growth. 34 However, in the presence of Bax-c-myc, the expression of tBid increased the kinetics of Bax-c-myc-induced cell death, 34 showing that tBid is able to amplify the killing function of an active form of Bax.…”
Section: Discussionmentioning
confidence: 94%
“…The specific molecular mechanisms through which Bax may be involved in regulation of cardiolipin peroxidation have not been established yet, although previous studies have elucidated that Bax acts upstream of accumulation of ROS [3,4,26] that required for lipid peroxidation. Recently, we reported that mitochondria targeted electron scavengers -hemigramicidin S conjugated nitroxides -prevented both superoxide accumulation and CL peroxidation and apoptosis initiated by ActD or irradiation without affecting Bax translocation [27,28].…”
Section: Recombinant Bax Increases Mitochondrial Peroxidase Activitymentioning
confidence: 99%
“…It has been reported that Bax acts upstream of increased reactive oxygen species (ROS) production in nerve growth factor-deprived neurons and that Bax induced ROS burst is both necessary and sufficient for cyt c redistribution in these cells [3]. Priault et al [4] suggested that Bax induced cell death is related to generation of ROS and membrane lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies link pro-apoptotic Bax to increased oxidative stress. In one study, Bax expression increased mitochondrial lipid oxidation and this event was necessary for Bax-induced cell death [13]. In studies of sympathetic neurons, Bax expression was required for ROS generation after nerve growth factor (NGF) withdrawal and the ROS production was upstream of the cell death commitment point [14].…”
Section: Introductionmentioning
confidence: 99%